BEAUTIFUL WRITING IS BASIS OF PRIMARY EDUCATION - Onakhon Jabborova; Gulhayo Torayeva (Western European Studies, 2024)
The article discusses the fact that "Husnikhat" is the basis of primary educational subjects, this approach is proven scientifically and methodologically, and the most relevant methodical tasks in this matter are defined
Keywords: Husnikhat; elementary; education; study